Calcium Requirements of Bovanes Hens - Ahmad, Hafiz Anwar; Yadalam, S.S.; Sr., D.A. Roland (International Journal of Poultry Science, 2003)
Calcium requirements of laying hens have been widely studied yet keep challenging nutritionists as a result of new genetic make-ups of commercial strains, farm management techniques, environmental concerns, and economics considerations. The present research was conducted to determine the calcium requirement of "Bovines" hens that represent about 17% of US layer industry. Increasing dietary level of calcium from 2.5 to 5.0% in hens` diets in increments of 0.5% had a significant positive linear effect on egg production and egg specific gravity. Increasing dietary calcium level from 2.5 to 5.0% increased egg production from 75.3 to 82.4% and egg specific gravity from 1.078 to 1.083 units. Calcium level had no effect on feed consumption or egg weight. "Bovines" hens required 5.57 g calcium/h/d for a maximum egg specific gravity index of 1.083 units (high shell quality). The decision to feed this level of calcium to achieve maximum shell quality however depends upon the nature and cost-benefits analysis of the layer operation.